Pengalaman Mahasiswa dalam Menggunakan Pinjaman Online (Studi pada Mahasiswa Perguruan Tinggi Surabaya) - Tridova, Avin Lois (Paradigma, 2025)
The rapid advancement of digital technology has fostered the emergence of technology-based financial services, known as financial technology (fintech), one of which is online lending or peer-to-peer (P2P) lending. The ease of access, fast process, and minimal requirements have made this service increasingly popular, including among university students. However, behind this convenience lies a significant risk of students becoming trapped in a cycle of debt. This study aims to explore the lived experiences of university students who use online lending services and to understand the meaning they derive from those experiences. The research uses a qualitative approach with Edmund Husserl’s phenomenological method, which emphasizes individuals’ subjective interpretations of their experiences. Data were collected through in-depth interviews with seven active university students in Surabaya who had previously or were currently using online lending services. The results show that students use these services for various reasons, including urgent financial needs, consumptive lifestyle, peer pressure, and being misled or scammed by others. The structure of experience (noesis) involves ease of access, anxiety, regret, and even dependency. Meanwhile, the meaning of the experience (noema) includes greater awareness of financial management, reflection on impulsive decisions, and a growing sense of financial responsibility and independence. These findings indicate that online lending has become a complex social phenomenon among students. Therefore, there is an urgent need to improve financial literacy and enforce stricter regulations to protect vulnerable groups such as students from financial exploitation.